Connexin45 modulates the proliferation of transit-amplifying precursor cells in the mouse subventricular zone - Khodosevich, Konstantin; Zuccotti, Annalisa; Kreuzberg, Maria Mechthild; Le Magueresse, Corentin; Monyer, Hannah (Proceedings of the National Academy of Sciences of the United States of America, 2012)
Connexins have been implicated in the regulation of precursor cell migration and proliferation during embryonic development of the mammalian brain. However, their function in postnatal neurogenesis is unclear. Here we demonstrate that connexin (Cx) 45 is expressed in transit-amplifying cells and neuroblasts in the postnatal subventricular zone (SVZ) and modulated the proliferation of SVZ-derived precursor cells in vivo. Thus, overexpression of Cx45 by retroviral injections increased the proliferation of Mash-1-positive transit-amplifying precursor cells in the SVZ. Conversely, conditional deletion of Cx45 in precursor cells decreased proliferation. Finally, we established that Cx45 positively influences cell cycle reentry via ATP signaling that involves intracellular calcium stores and ERK1/2 signaling. Author Information Konstantin Khodosevicha,1, Annalisa Zuccottia,1, Maria M. Kreuzberga, Corentin Le Magueressea, Marina Frankb, Klaus Willeckeb, and Hannah Monyera,2aDepartment of Clinical Neurobiology, University Hospital and German Cancer Research Center (DKFZ) Heidelberg, 69120 Heidelberg, Germany; andbLife and Medical Sciences (LIMES) Institute, University of Bonn, Carl-Troll-Strasse 31, 53115 Bonn, GermanyEdited by Michael V. L. Bennett, Albert Einstein College of Medicine, Bronx, NY, and approved October 30, 2012 (received for review October 1, 2012) Footnotes↵1K.K. and A.Z. contributed equally to this work.↵2To whom correspondence should be addressed. E-mail: h.monyerdkfz-heidelberg.de.Author contributions: K.K., A.Z., M.M.K., and H.M. designed research; K.K., A.Z., M.M.K., and C.L.M. performed research; M.F. and K.W. contributed new reagents/analytic tools; K.K., A.Z., M.M.K., C.L.M., and H.M. analyzed data; and K.K., A.Z., and H.M. wrote the paper.The authors declare no conflict of interest.This article is a PNAS Direct Submission.This article contains supporting information online at www.pnas.org/lookup/suppl/doi:10.1073/pnas.1217103109/-/DCSupplemental.